THE CONTENT OF THE DEVELOPMENT OF INFORMATION CULTURE OF FUTURE TEACHERS OF TECHNOLOGICAL EDUCATION THROUGH MEDIA LITERACY (Scientific journal of the Fergana State University, 2024)
This article is about the globalization of media education and the wide spread of media literacy among people, especially among young people. Media is a formative part of working with information. Mass communication and information system is the most effective system of acquiring knowledge. Currently, the media is considered the most convenient for receiving, distributing and delivering information to the right places. Among mass media, television, internet, radio and press are the most important. Today, media is considered an integral part of human life because it increases the effectiveness of education. In addition, the role of media in distance education and online classes is very large.